2021
DOI: 10.1021/acsomega.0c06276
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Water-Soluble Silver Sulfide Quantum Dots and Their Application to Bioimaging

Abstract: This work reports a simple water-phase microwave method for the synthesis of water-soluble red emission Ag2S quantum dots at low temperatures without the need for an anaerobic process. It is worth noting that the prepared water-soluble Ag2S quantum dots enjoy positive water dispersion stability. 3-(4,5)-Dimethylthiahiazo­(-z-y1)-3,5-di-phenytetrazoliumromide (MTT) results showed that the prepared Ag2S quantum dots had promising biocompatibility and low cytotoxicity. In addition, we further applied the low-toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…28 However, the XRD morphology corresponding to that of the Ag 2 S crystal indicated that the product was Ag 2 S QDs. 35 The CsPbBr 3 QD XRD pattern exhibited peaks at (100), (110), ( 200), ( 210), (211), and (220), which was consistent with the standard pattern and corresponded to the cubic structure of CsPbBr 3 QDs. 36 As shown in Figure 2b, Ag 2 S QDs showed a significant absorption coefficient for light with photon energies greater than 1 eV or wavelengths shorter than 1040 nm.…”
Section: Resultssupporting
confidence: 76%
“…28 However, the XRD morphology corresponding to that of the Ag 2 S crystal indicated that the product was Ag 2 S QDs. 35 The CsPbBr 3 QD XRD pattern exhibited peaks at (100), (110), ( 200), ( 210), (211), and (220), which was consistent with the standard pattern and corresponded to the cubic structure of CsPbBr 3 QDs. 36 As shown in Figure 2b, Ag 2 S QDs showed a significant absorption coefficient for light with photon energies greater than 1 eV or wavelengths shorter than 1040 nm.…”
Section: Resultssupporting
confidence: 76%
“…In this context, our group has found that the gallium sulfide (GaS x ) shell effectively removes the defect levels on the AgInS 2 cores, and the core/shell QDs exhibit a narrowband emission with a PL quantum yield (QY) of as high as 56%. 13 The spectral width of the AgInS 2 /GaS x core/shell QDs are almost comparable or still narrower than other types of cadmium-free QDs, such as indium phosphide 14,15 and silver sulfide 16,17 QDs. Such narrowband emission can be demonstrated in the visible spectral range by compositional tuning.…”
Section: Introductionmentioning
confidence: 96%
“…These findings confirm that SB-Ag 2 S QDs have been successfully synthesized by a facile one-pot synthesis method, implying that the SBs could chelate Ag + and that the complexes were further neutralized by S − ions and crystallized to form SB-Ag 2 S QDs. The formation, crystal structure, and physical characteristics of these Ag 2 S QDs capped with Schiff base ligands synthesized by the one-pot synthesis method are similar to those of other Ag 2 S QDs capped with BSA, 59 TGA, 53 2-MPA, 30 3-MPA, 10 d -penicillamine, 31 alkyl, 3 2-(benzylidene amino)benzothiol, 37 and EDTA 38 prepared via one-pot synthesis, one-pot microwave assisted reaction, pyrolysis, chemical condensation, solvothermal, and hydrochemical bath deposition methods. Nevertheless, the particle sizes of SB-Ag 2 S QDs (4.0–5.6 nm) synthesized by our one-pot synthesis tend to be smaller as compared those Ag 2 S QDs prepared with the other methods, such as alkyl-Ag 2 S QDs (10.2 nm) via pyrolysis, 3 2-(benzylidene amino) benzothiol-Ag 2 S QDs (42 nm) via solvothermal, 37 and EDTA-Ag 2 S QDs (10–20 nm) via hydrochemical bath deposition.…”
Section: Resultsmentioning
confidence: 63%
“…8,27,28 For this reason Ag 2 S has oen been used as an electron injector or shuttle in hybrid catalytic and light harvesting systems. 27,28 Size-controlled Ag 2 S QDs have been synthesized by various methods, including the single precursor, 3 one-pot synthesis, 29 hydrothermal, 30 water-phase microwave, 31 liquid-liquid interface reaction, 32 and reverse microemulsion methods. 33,34 The capping agents used to passivate the atoms on the QD surface, which are important to stabilize and prevent the nanocrystalline structures from aggregating, include surfactant (cetyltrimethyl ammonium bromide), 35 sodium dodecyl sulfate, 36 Schiff-base (2-(benzylidene amino)azobenzothiol) ligand, 37 ethylenediaminetetraacetic acid (EDTA), 38 2-mercaptopropioic acid (2-MPA), 10,39 thioglycolic acid (TGA), 40 and or a carboncontaining shells.…”
Section: Introductionmentioning
confidence: 99%